Dendrimers and Dendritic Materials against Infectious Diseases - Francisco Javier de La Mata; Paula Ortega; Sandra García-Gallego (MDPI AG, 2022)
The COVID-19 pandemic showed more deeply the need of our society to provide new therapeutic strategies to fight infectious diseases, not only against currently known illnesses, where common antibiotics and drugs appear to be not fully effective, but also against new infectious threats that may arise [...]